Advancing the Care Experience for patients receiving Palliative care as they Transition from hospital to Home (ACEPATH): Codesigning an intervention to improve patient and family caregiver experiences - Madeline McCoy; Taylor Shorting; Vinay Kumar Mysore; Edward Fitzgibbon; Jill Rice; Meghan Savigny; Marianne Weiss; Daniel Vincent; Meaghen Hagarty; Krystal Kehoe MacLeod; Natalie C. Ernecoff; Rex Pattison; et al. (Wiley, 2024)
Abstract Background Returning home from the hospital for palliative‐focused care is a common transition, but the process can be emotionally distressing and logistically challenging for patients and caregivers. While interventions exist to aid in the transition, none have been developed in partnership with patients and caregivers. Objective To undergo the initial stages of codesign to create an intervention (Advancing the Care Experience for patients receiving Palliative care as they Transition from hospital to Home [ACEPATH]) to improve the experience of hospital‐to‐home transitions for adult patients receiving palliative care and their caregiver(s). Methods The codesign process consisted of (1) the development of codesign workshop (CDW) materials to communicate key findings from prior research to CDW participants; (2) CDWs with patients, caregivers and healthcare providers (HCPs); and (3) low‐fidelity prototype testing to review CDW outputs and develop low‐fidelity prototypes of interventions. HCPs provided feedback on the viability of low‐fidelity prototypes. Results Three patients, seven caregivers and five HCPs participated in eight CDWs from July 2022 to March 2023. CDWs resulted in four intervention prototypes: a checklist, quick reference sheets, a patient/caregiver workbook and a transition navigator role. Outputs from CDWs included descriptions of interventions and measures of success. In April 2023, the four prototypes were presented in four low‐fidelity prototype sessions to 20 HCPs. Participants in the low‐fidelity prototype sessions provided feedback on what the interventions could look like, what problems the interventions were trying to solve and concerns about the interventions. Conclusion Insights gained from this codesign work will inform high‐fidelity prototype testing and the eventual implementation and evaluation of an ACEPATH intervention that aims to improve hospital‐to‐home transitions for patients receiving a palliative approach to care. Patient or Public Contribution Patients and caregivers with lived experience attended CDWs aimed at designing an intervention to improve the transition from hospital to home. Their direct involvement aligns the intervention with patients' and caregivers' needs when transitioning from hospital to home. Furthermore, four patient/caregiver advisors were engaged throughout the project (from grant writing through to manuscript writing) to ensure all stages were patient‐ and caregiver‐centred.